Effectiveness of Behavioral Parent Therapy in Preschool Children With Attention-Deficit Hyperactivity Disorder - Huei-Lin Huang (Kaohsiung Journal of Medical Sciences, 2009)
The purpose of this study was to assess the effectiveness of a behavioral parent therapy (BPT) program in children with attention-deficit hyperactivity disorder (ADHD) using multidimensional evaluations, the Child Behavior Checklist (CBCL) and the Teacher Report Form (TRF). Between 2001 and 2005, the parents of 21 preschool children with ADHD were divided into six groups and participated in a series of 11 BPT sessions. Before and after BPT, the parents completed the CBCL, and the teachers completed the TRF. The behavioral and emotional problems of the children showed improvement after the BPT sessions, specifically for the following categories: internalizing problems, anxious/depressed syndromes, somatic complaints, externalizing problems, rule-breaking behaviors, aggressive behaviors, social problems, thought problems, and attention problems. In the DSM-oriented scale of the CBCL, affective problems, anxiety problems, somatic problems, ADHD problems, oppositional defiant disorder problems, and conduct disorder problems showed significant improvements. On the DSM scale of the TRF, Inattention syndrome improved significantly after the BPT sessions, while other syndromes showed non-significant changes. We conclude that the BPT program significantly improved the children's behavioral problems at home and inattention problems at school.